Exploring the future of virtual reality and gamification in learning enviornments: Students motivation and engagement in higher education - Angelino, F.; Loureiro, S. M. C.; Bilro, R. G. (CEISEE 2019: 15th China-Europe International Symposium on Software Engineering Education, Conference proceedings, 2019)
Virtual reality and gamification - the application of game-based techniques in non-game environments -, have been the subject of a growing interest from scholars and practitioners regarding its application in several areas, namely in Higher Education. In fact, a growing number of researches concerning virtual reality and gamification and its applications to this area have been published since 2012. Following this pathway, this research aims to identify and propose practical applications of virtual reality and gamification in higher education environments, which can contribute with a positive input to students’ engagement and motivation towards their learning and academic activities. To do so, we employed a mixed research technique (qualitative and quantitative) in this research, collecting data from first year students and faculty staff at Higher Education Institutions (HEI). The collected data will then be processed and analyzed using specific software tools (MAXQDA and SPSS). With this research we pretend to put in evidence that an enormous pathway is here to be uncovered, which may expose virtual reality a gamification as contributors of creating stimuli that enhance students’ experiences from the learning environments, and in result may lead to influence decision-making to actual and prospective students’ intentions.